Analisis Pengaruh Infrastruktur Jalan dan Kepadatan Penduduk Terhadap Pendapatan Per Kapita di Pulau Sumatera - Alvina, Cut Aja; Triani, Mike (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to examine and analyze the effect of road infrastructure and population density on per capita income in 10 provinces on the island of Sumatra. The type of data used in this study is secondary data sourced from the Indonesian Central Statistics Agency (BPS) and other related agencies. In this study, panel data regression analysis techniques were used using the Random Effect Model (REM) method with cross-sectional data obtained from 10 provinces on Sumatra Island as well as combined time series data for the period 2015 to 2022. The results of this study found that (1) road infrastructure has a negative and significant effect on income per capita on the island of Sumatra. (2) Population Density has a positive and significant effect on Per Capita Income on Sumatra Island.